2015
DOI: 10.1097/md.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width Levels Correlate With Liver Fibrosis and Inflammation

Abstract: We aimed to study whether red blood cell distribution width (RDW) could be one of the variables determining the extent of liver fibrosis and inflammation in patients with biopsy-proven hepatitis B.A total of 446 hepatitis B virus-infected patients who underwent liver biopsy were divided into 2 groups: absent or mild and moderate–severe according to the severity of liver fibrosis and inflammation. The independent variables that determine the severity of liver fibrosis and inflammation were explored.RDW values i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 39 publications
(53 reference statements)
0
34
0
Order By: Relevance
“…Previous studies have identified RDW as an accurate predictor of inflammatory status of hepatitis B-infected patients, mortality of acute pancreatitis, and activity of inflammatory bowel disease [24, 26, 35]. Moreover, elevated RDW were found to be an indicator of risk and progression of multiple malignancies, while the prognostic value of RDW has also been discussed [28, 29, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified RDW as an accurate predictor of inflammatory status of hepatitis B-infected patients, mortality of acute pancreatitis, and activity of inflammatory bowel disease [24, 26, 35]. Moreover, elevated RDW were found to be an indicator of risk and progression of multiple malignancies, while the prognostic value of RDW has also been discussed [28, 29, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive predictive models of fibrosis are therefore needed. Single markers have been proposed such as platelet count, AST and ALT, gamma-globulins, serum HBsAg levels, CP, red blood cell distribution width, Interleukin-2R, TGF-α, serum Golgi protein 73 (GP73), and miR-122[13,14,16,17,25,28-31]. However, currently, none of these markers are sufficiently liver-specific enough to accurately reflect fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It appears in the viremia caused by different viruses: Hepatitis C virus [25], cytomegalovirus [26], by some hemorrhagic fever viruses [27,28]. Causes of hemolysis in viral diseases may be the following factors: Pathological immune response, as a type of acute autoimmune reaction [29], direct or indirect action of the virus on erythrocytes [30], the incidence of precursors of erythropoiesis [31], etc. There are two-ways in which the direct effect of the virus on the RBCs can happen: Direct infection of erythrocytes and/or hemadsorption.…”
Section: Discussionmentioning
confidence: 99%